Pengaruh Struktur Modal dan Leverage terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening - Sentri Lestiani; Ati Retna Sari; Supami Wahyu Setyowati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the effect of capital structure and leverage on firm value with financial performance as an intervening variable. Data were collected through the IDX website on companies in the goods and consumer sectors in 2021-2024 and analyzed using SmartPLS. The results show that capital structure and leverage affect firm value through financial performance. This study recommends that corporate decisions in financial management related to debt need to be considered with the company's financial performance to minimize corporate risk.